A Biodegradable Magnetic Microrobot Based on Gelatin Methacrylate for Precise Delivery of Stem Cells with Mass Production Capability. Issue 25 (23rd May 2022) - Noh, Seungmin; Jeon, Sungwoong; Kim, Eunhee; Oh, Untaek; Park, Danbi; Park, Sun Hwa; Kim, Sung Won; Pané, Salvador; Nelson, Bradley J.; Kim, Jin‐young; Choi, Hongsoo
Abstract: A great deal of research has focused on small‐scale robots for biomedical applications and minimally invasive delivery of therapeutics (e.g., cells, drugs, and genes) to a target area. Conventional fabrication methods, such as two‐photon polymerization, can be used to build sophisticated micro‐ and nanorobots, but the long fabrication cycle for a single microrobot has limited its practical use. This study proposes a biodegradable spherical gelatin methacrylate (GelMA) microrobot for mass production in a microfluidic channel. The proposed microrobot is fabricated in a flow‐focusing droplet generator by shearing a mixture of GelMA, photoinitiator, and superparamagnetic iron oxide nanoparticles (SPIONs) with a mixture of oil and surfactant. Human nasal turbinate stem cells (hNTSCs) are loaded on the GelMA microrobot, and the hNTSC‐loaded microrobot shows precise rolling motion in response to an external rotating magnetic field. The microrobot is enzymatically degraded by collagenase, and released hNTSCs are proliferated and differentiated into neuronal cells. In addition, the feasibility of the GelMA microrobot as a cell therapeutic delivery system is investigated by measuring electrophysiological activity on a multielectrode array. Such a versatile and fully biodegradable microrobot has the potential for targeted stem cell delivery, proliferation, and differentiation for stem cell‐based therapy. Abstract : A magnetically controlled GelMA‐based biodegradable microrobot is developed for targeted stem cell therapy. The microrobots composed of SPIONs and GelMA are fabricated with a droplet generator. The stem cell‐loaded microrobot demonstrates magnetic actuation, enzymatic biodegradation, and cell release. The proliferation, neuronal differentiation, and electrophysiological activity are also investigated. Such a mass‐producible microrobot will have considerable potential for targeted stem cell therapy.